Cornici pedagogiche per la formazione docente Il ruolo dell'insegnante di sostegno nella co-costruzione di contesti inclusivi - Amatori, Gianluca (Traiettorie inclusive - Open Access, 2019)
The volume reviews the fundamental issues of teacher training, especially about the support teacher, to re-establish new coordinates for the co-construction of inclusive class contexts.